2021
DOI: 10.1262/jrd.2020-137
|View full text |Cite
|
Sign up to set email alerts
|

Differentially methylated CpG sites related to fertility in Japanese Black bull spermatozoa: epigenetic biomarker candidates to predict sire conception rate

Abstract: For semen suppliers, predicting the low fertility of service bull candidates before artificial insemination would help prevent economic loss; however, predicting bull fertility through in vitro assessment of semen is yet to be established. In the present study, we focused on the methylated CpG sites of sperm nuclear DNA and examined methylation levels to screen new biomarkers for predicting bull fertility. In frozen-thawed semen samples collected from Japanese Black bulls, for which the sire conception rate (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…These findings are in alignment with similar studies in humans and domesticated animals (Costes et al, 2022;Rotondo et al, 2021;Štiavnická et al, 2022;Sujit et al, 2020;Takeda et al, 2021), which have all highlighted the critical role of DNA methylation in the proper development and functioning of sperm cells. Candidate genes that we identified from gene networks built from DMclusters in sperm are well-studied and known to be involved in the regulation of developmental onset via epigenetic transcriptional repression in humans and mice, specifically in the multi-protein complexes formed by JARID2 and EZH2 in PRC2 (Fischer et al, 2022;Margueron & Reinberg, 2011;Pasini et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in alignment with similar studies in humans and domesticated animals (Costes et al, 2022;Rotondo et al, 2021;Štiavnická et al, 2022;Sujit et al, 2020;Takeda et al, 2021), which have all highlighted the critical role of DNA methylation in the proper development and functioning of sperm cells. Candidate genes that we identified from gene networks built from DMclusters in sperm are well-studied and known to be involved in the regulation of developmental onset via epigenetic transcriptional repression in humans and mice, specifically in the multi-protein complexes formed by JARID2 and EZH2 in PRC2 (Fischer et al, 2022;Margueron & Reinberg, 2011;Pasini et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…DNA methylation has been linked as both a cause and consequence to variation in gene regulation (Pacis et al., 2019), has been studied prolifically as a key biomarker for aging and disease for several decades (Mattei et al., 2022; Prado et al., 2021), and is associated with variation in reproductive metrics in humans, model laboratory organisms, and commercially relevant species (Rotondo et al., 2021; Sujit et al., 2020). Recent studies have identified an increasingly important role for DNA methylation variation in sperm to fertility metrics in the ex situ breeding of domesticated animals (Costes et al., 2022; Štiavnická et al., 2022; Takeda et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kropp et al [ 34 ] analysed the methylome of sperm from pools of low and high-fertility bulls by Methyl-CpG-binding domain sequencing and showed that DNA was hypomethylated in sperm from low-fertility bulls; moreover, they identified 98 differentially expressed genes in blastocysts derived from sperm of those bulls. Takeda et al [ 35 ] used a human methylation microarray and reported a relationship between sire conception rate and DNA methylation with 147 differently methylated cytosines (DMCs) and 10 differently methylated regions (DMRs) between low- and high-fertility Japanese Black bulls. The relationship of bull sperm quality and DNA methylation was reported by Capra et al [ 36 ], who showed that sperm with low and high motility differed in DNA methylation of genes involved in the maintenance of chromatin structure.…”
Section: Introductionmentioning
confidence: 99%
“…Rekawiecki et al assessed the percentage of methylation in the promoters of progesterone receptor isozymes A (PGRA) and B (PGRB) and determined that the hypermethylation level of the promoter region of the PGRA subtype might be a mechanism for regulating the inhibition of PGRB activity by PGRA, which may affect the regulation of progesterone in the luteum and endometrium [107]. Takeda used frozen semen samples from Japanese black bulls to record the sire conception rate (SCR), and a human methylation gene chip was used to analyze the methylation level of each CpG site [108]. The results showed significant differences in the methylation of 143 CpG loci related to SCR.…”
Section: Studies On Dna Methylation Associated With Reproduction In C...mentioning
confidence: 99%